Salience in Experimental Tests of the Endowment Effect - Bordalo, Pedro; Gennaioli, Nicola; Shleifer, Andrei (American Economic Review, 2012)
We provide a novel account of experimental evidence for the endowment effect using the salience mechanism (Bordalo, Gennaioli, and Shleifer, 2011). The two-stage procedure implemented in experiments implies that the endowed good and other goods are evaluated in different contexts. We describe conditions under which the standard effect occurs, but also account for recent evidence such as a reverse endowment effect for bads and a role for reference prices in modulating the WTA-WTP gap.